2016
DOI: 10.1155/2016/4048390
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Concept of NAD Redox Balance for Cisplatin Nephrotoxicity

Abstract: Cisplatin is a widely used chemotherapeutic agent for the treatment of various tumors. In addition to its antitumor activity, cisplatin affects normal cells and may induce adverse effects such as ototoxicity, nephrotoxicity, and peripheral neuropathy. Various mechanisms such as DNA adduct formation, mitochondrial dysfunction, oxidative stress, and inflammatory responses are closely associated with cisplatin-induced nephrotoxicity; however, the precise mechanism remains unclear. The cofactor nicotinamide adenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 116 publications
(148 reference statements)
2
33
0
2
Order By: Relevance
“…NF-κB can mediate inflammatory response, by affecting the expression of a large number of proinflammatory mediators such as TNF-α, COX-2 and inducible nitric oxide [35]. Cisplatininduced ROS production activates NF-B, which in turn induces the production of proinflammatory cytokines [36]. In the current study, the cisplatin-treated group showed a pro-inflammatory response as evidenced by significant increase in NF-kB expression.…”
Section: Discussionmentioning
confidence: 51%
“…NF-κB can mediate inflammatory response, by affecting the expression of a large number of proinflammatory mediators such as TNF-α, COX-2 and inducible nitric oxide [35]. Cisplatininduced ROS production activates NF-B, which in turn induces the production of proinflammatory cytokines [36]. In the current study, the cisplatin-treated group showed a pro-inflammatory response as evidenced by significant increase in NF-kB expression.…”
Section: Discussionmentioning
confidence: 51%
“…The Nox family consists of seven members (Noxs 1–5, Duox1 and 2). Nox2 and Nox4 are highly expressed within the kidney and Nox4 is known as the predominant form, which plays important roles in renal oxidative stress and kidney injury (Gill and Wilcox, 2006; Sedeek et al, 2013; Kim et al, 2016; Oh et al, 2016). Our data show that lentivirus-mediated knockdown of Nox4 in vivo significantly attenuated cisplatin nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage is one of the important pathogeneses by which cisplatin triggers kidney tissue injury [27]. In mice kidney tissues, cisplatin significantly increased oxidative stress marker 3-NT expression (Figure 4(a)) and inhibited antioxidant enzyme activities, including T-SOD and GSH-Px (Figures 4(b) and 4(c)), compared with the control group.…”
Section: Aps Attenuates Cisplatin-induced Oxidative Damage In Mice Kimentioning
confidence: 99%